2017
DOI: 10.1111/lest.12144
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary vaccination: the pandemic effect

Abstract: Justification of a voluntary vaccination policy in England and Wales rests on tenuous foundations. Two arguments against voluntary vaccination are gaining ground. The first is that globalisation necessitates preparedness strategies for pandemics. Assuming sufficient supply, compulsory vaccination of adults and children constitutes a potential policy option in the context of a severe, vaccine‐preventable pandemic outbreak. The second argument is that children have a right to preventive medicine and thus to vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
1
19
0
1
Order By: Relevance
“…Our study demonstrated a high level of over 65-year-old people vaccinated/willing to be vaccinated against COVID-19; however, a lower vaccine acceptance was associated to the date of questionnaire fulfilling (after the mandatory implementation of the green pass). Therefore, although this evidence needs to be further confirmed, it is possible to agree with previous studies reporting that compulsory measures must be accompanied by effective education and information strategies of the target population [20,43], paying attention to the spread of data not supported by scientific evidence [18]. In this context, the role of reference healthcare personnel is crucial.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our study demonstrated a high level of over 65-year-old people vaccinated/willing to be vaccinated against COVID-19; however, a lower vaccine acceptance was associated to the date of questionnaire fulfilling (after the mandatory implementation of the green pass). Therefore, although this evidence needs to be further confirmed, it is possible to agree with previous studies reporting that compulsory measures must be accompanied by effective education and information strategies of the target population [20,43], paying attention to the spread of data not supported by scientific evidence [18]. In this context, the role of reference healthcare personnel is crucial.…”
Section: Discussionsupporting
confidence: 78%
“…In this scenario, the Italian government chose to adopt the mandatory green pass to ensure the safe recovery of social and economic activities from COVID-19 pandemic. However, it is demonstrated that mandatory measures such as the compulsory adoption of a vaccine passport may be interpreted as a threat to human rights and civil liberty, and then decrease vaccine acceptance [43]. Therefore, interventions supporting individuals' autonomous motivation to get vaccinated should be programmed and implemented beside compulsory previsions of law, even in non-pandemic times [20,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The realistic possibility of other pandemics raises important question about whether we have a moral obligation, and indeed we should have a legal obligation, to contribute to the realization of herd immunity when we do have a vaccine that can prevent or stop them. 16 Indeed, even seasonal flu outbreaks, which do not reach pandemic levels, often entail a large collective cost, even for those who do not get the flu. For instance, it has been estimated that the economic impact of annual influenza epidemics in the USA, taking into account loss of earning, would amount to US$87.1 billion.…”
Section: Herd Immunity As a Public Goodmentioning
confidence: 99%
“…It is commonly accepted that in these cases children have a right to be protected from preventable harm, which implies a right to preventive medicine. 16 Arguably, it is a parents’ and a state’s responsibility to take reasonable steps to ensure that children’s health is protected. The argument is weaker when it comes to adult vaccination, since competent adults have a prima facie right to make their own autonomous decisions about their health and the risks they want to take on themselves.…”
Section: Harm Preventionmentioning
confidence: 99%